EVALUASI IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI - Erfy Melany Lalupanda (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2019)
Abstract: The purpose of this study is to evaluate the implementation of the Operational Cost Program for the Implementation of Early Childhood Education (BOP PAUD). Evaluation research uses the Discrepancy model, which measures the gap between the process of implementing the BOP PAUD fund program and the procedures stipulated in Regulation of the Minister of Education and Culture Number 2 of 2016 concerning Technical Guidelines for the Use of Operational Funds for the Implementation of Early Childhood Education. Evaluation based on the design of the implementation of the BOP PAUD program process, includes: planning, implementation and accountability. The approach in this study is descriptive qualitative with interview data collection techniques and document studies in the form of School Activity and Budget Plans and Accountability Reports. The results of the study, namely: there is a gap in the implementation of the BOP PAUD program in the planning process, channeling of funds, and reporting of fund accountability. The cause of the gap is that BOP PAUD fund managers have not followed the system regulated in financing management.